PERAN PEKERJA PEREMPUAN DALAM USAHA EKONOMI MIKRO PENGOLAHAN JAMBU METE DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA MOKO KECAMATAN LAKUDO KABUPATEN BUTON TENGAH - Alang, Alang; Arsyad, Muhammad; Yusuf, Bakri (WELL-BEING: Journal of Social Welfare, 2022)
This study aims to determine the role of women workers in the micro-economic business of cashew processing in Moko Village, in improving family welfare. And knowing the factors that influence the role of female cashew processing workers in Moko Village in improving family welfare. This type of research is descriptive qualitative research. Data collection techniques were carried out by means of observation, interviews, and documentation with research informants as many as 10 female workers in Moko Village, Lakudo District who worked in cashew processing.The results showed that the social role of female workers in cashew processing in Moko Village was active in social activities in the community as a form of fulfilling social needs, the role in cashew processing of female workers in addition to acting outside as a teacher and so on they can also act as workers by following all the provisions, especially in the realm of social interaction among their workers. . The public role of women workers in cashew processing in Moko Village is not only as workers in cashew processing, but they try as much as possible, establishing businesses to increase the family economy and prosper their families. In terms of this public role, cashew processing carries out community activities, one of which is commemorating religious holidays and the women working women there have a role in preparing all consumption needs together for the realization of these public events. The domestic role of female workers in cashew processing in Moko Village still prioritizes the family. Even though they work due to lack of economic factors, it does not become an obstacle to gathering with their families. and often participates in every activity that is carried out by the people around him by participating in majlis ta'lim activities. which is a form of activity to fulfill social needs. In the processing of cashew, these women workers are too obvious because most of them are employed workers so that their domestic role does not have a clear enough role in the processing of cashew.Internal factors that affect female workers in cashew processing in Moko Village are due to the compulsion of life that forces female workers to work in improving economic conditions in improving family welfare even though they consider working in cashew processing difficult but again the condition of the family to support. External factors that influence female workers in the processing of cashew nuts in Moko Village in improving family welfare are seen from the encouragement of their husbands. Relational factors that affect female workers, most of them have acquaintances with important people in supporting the welfare of their families.